Etika Profesi Guru terhadap Pembentukan Karakter Siswa - Munawir, Munawir; Sari, Dewi Citra Puspita; Fitria, Intan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the role of teacher professional ethics in the formation of student character through a systematic review of scientific journal literature. Teacher professional ethics, which include integrity, responsibility, fairness, and caring, are believed to have a significant influence on student character development. This review identifies how teachers who uphold professional ethics can be positive role models, create a safe and supportive learning environment, and instill important moral and social values. The results of the review indicate that teacher professional ethics not only have an impact on student academic achievement, but also on character development such as honesty, discipline, empathy, and social responsibility. This study emphasizes the importance of ongoing professional ethics training for teachers and the need for a strong support system to ensure the implementation of professional ethics in daily educational practices.